Health and healing in world religions - McCann, Gillian, 1965- author. Link
1 online resource
Keywords: "Health and Healing in World Religions is a comprehensive introduction to the field that explores the research that links spirituality and well-being, including work with addiction and trauma. Each chapter includes an introduction to and summary of each tradition, questions at the conclusion, and boxes that highlight key ideas from the chapter using an example and interviews with medical professionals and other healers. Health and Healing in World Religions looks at cutting edge interfaces between spirituality and health such as mindfulness practices, addiction programmes, indigenous approaches to healing, traditional Chinese medicine, yoga and Ayurveda and more. The text provides an overview of the research and practice all in one place and includes extensive bibliographies and resource guides for ease of reference. Health and Healing in World Religions is derived from over twenty years of teaching and research in health and healing and comes from an in-depth understanding of religion and spirituality. It is a vital guide to understanding cultural competency in the healing professions and the need to understand the cultural and spiritual traditions of clients"--